Design, Synthesis and Anticandidal Evaluation of Indazole and Pyrazole Derivatives - Karen Rodríguez-Villar; Alicia Hernández-Campos; Lilián Yépez-Mulia; Teresita del Rosario Sainz-Espuñes; Olivia Soria-Arteche; Juan Francisco Palacios-Espinosa; Francisco Cortés-Benítez; Martha Leyte-Lugo; Bárbara Varela-Petrissans; Edgar A. Quintana-Salazar; Jaime Pérez-Villanueva (MDPI AG, 2021)
Candidiasis, caused by yeasts of the genus Candida, is the second cause of superficial and mucosal infections and the fourth cause of bloodstream infections. Although some antifungal drugs to treat candidiasis are available, resistant strains to current therapies are emerging. Therefore, the search for new candicidal compounds is certainly a priority. In this regard, a series of indazole and pyrazole derivatives were designed in this work, employing bioisosteric replacement, homologation, and molecular simplification as new anticandidal agents. Compounds were synthesized and evaluated against C. albicans, C. glabrata, and C. tropicalis strains. The series of 3-phenyl-1H-indazole moiety (10a-i) demonstrated to have the best broad anticandidal activity. Particularly, compound 10g, with N,N-diethylcarboxamide substituent, was the most active against C. albicans and both miconazole susceptible and resistant C. glabrata species. Therefore, the 3-phenyl-1H-indazole scaffold represents an opportunity for the development of new anticandidal agents with a new chemotype.